Influence of workplace flexibility on employee engagement among young generation - Shi Hao Lee; Chin Wei Chong; Adedapo Oluwaseyi Ojo (Cogent Business & Management, 2024)
Workplace flexibility has become increasingly popular and important within the landscape of human resource management especially during and even after the COVID19-pandemic among young working adults. The objective of this study is to identify the influence of four forms of workplace flexibility on employee engagement. The study used online questionnaire and were answered by 185 young working adults below 30 years old as of 2022 through Google Form. The data were analyzed by using partial least square (PLS) structural equation modelling (SEM) technique. The study found that workspace flexibility and operational flexibility have significant positive relationships with employee engagement. This study provides practical and direct implications for business and society. Besides that, this research also adds values to the understanding of workplace flexibility and employee engagement for human resource scholars.Young generation emphasizes on workplace flexibility than any older generations in this modern world. They value the importance of workplace flexibility and prioritize work-life balance than any generation before them. Furthermore, workplace flexibility is playing an important role in human resource management particularly during and after the COVID19-pandemic. Meanwhile, employee engagement which represents the attitude, dedication, commitment and satisfaction of an employee towards the job which eventually affects the performance and productivity of an organization is vital. Hence, we need to figure out whether workplace flexibility that demands by young generation will influence employee engagement that highlights by organization. This study found out that workspace flexibility and functional flexibility have significant positive relationships with employee engagement. Therefore, it is believed that win-win situation can be created through the implementation of workplace flexibility in certain extent which benefits the business world and society.
Keywords: 650; Workplace flexibility; employee engagement; working time flexibility; workspace flexibility; functional; flexibility; operational flexibility; young working adults